The Impact of Social Media Marketing and Financial Technology on MSME Performance in Ambon City - Jacsy Tubalawony; Hansen Hein Rumtutuly (West Science Interdisciplinary Studies, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in regional economic development, particularly in archipelagic areas such as Ambon City, which face geographical constraints and limited market access. This study aims to examine the impact of Social Media Marketing and Financial Technology on MSME performance in Ambon City. A quantitative explanatory approach was employed using survey data collected from 200 MSME owners who actively utilize social media and financial technology services. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that both Social Media Marketing and Financial Technology have positive and significant effects on MSME performance. Financial Technology demonstrates a more dominant influence by improving transaction efficiency, accelerating cash flow turnover, and enhancing financial management practices. Meanwhile, Social Media Marketing contributes to increasing product visibility, expanding market reach, and strengthening relationships with customers. Furthermore, the findings reveal that the integration of financial technology and digital marketing creates a synergistic effect that enhances overall MSME performance. These findings highlight the importance of adopting an integrated digital strategy to improve MSME competitiveness and sustainability in archipelagic regions. The study provides practical insights for MSME owners and policymakers in designing more effective digital empowerment strategies.